Neutrófilos têm um papel protetor durante os estágios iniciais da infecção por Leishmania amazonensis em camundongos BALB/c - Louisa Maria de Andrade e Sousa (2013)
Neutrophils are involved in early stages of immune response to pathogens. In the present work, we investigated the role of neutrophils during the establishment of Leishmania amazonensis infection in BALB/c and C57BL/6 mice. First, we have shown that there is an intense influx of neutrophils to the ears as early as 6 h after infection; maximum neutrophil accumulation was observed between 6 and 24 h. To investigate the role of neutrophils at the time of infection, we depleted neutrophils using either RB6-8C5 or 1A8 monoclonal antibodies. Neutrophil depletion lead to faster lesion development, associated with increased parasite numbers and higher arginase activity in BALB/c mice, but not in C57BL/6 mice. Increased susceptibility was also accompanied by augmented level of anti-L. amazonensis IgG1 and IgG2a production and increased production of IL-10. Inhibition of IL-10 signaling using anti-IL-10R abrogated the increase in parasite loads observed in neutrophil depleted mice, suggesting that parasite proliferation observed in the absence of neutrophils is mediated by IL-10. The increase in IL-10 levels seems to be at least in part dependent on the increase in IgG levels, since we have shown in vitro that immune complexes induce IL-10 production by macrophages and we have also demonstrated that treatment in vivo with anti-FcãR, which blocks immune complexes signaling, abolished the increase in IL-10 levels. Besides, promastigote forms of L. amazonensis were also able to induce IL-10 production by macrophages stimulated with LPS or HA by an ERK-dependent mechanism and this increase in IL-0 levels favored parasite replication inside its host cell. The effects of IL-10 on parasite replication do not seem to be caused by inhibition of IL-12, TNF-á or nitric oxide production, nor by the induction of arginase activity. Besides, neutrophil depletion reduced the accumulation of regulatory T cells, which are known to restrain lesion development during early L. amazonensis infection. Taken together, our data indicate that the presence of neutrophils at the time of infection guarantees parasite elimination, controls the productions of antibodies and cytokines, specially IL-10 that acts directly on macrophages favoring parasite growth, and maintains appropriate levels of regulatory T cells at the site of infection, leading to control of parasite numbers and limited lesion development during the first week of infection in BALB/c mice.